Don’t-Ask-Don’t-Tell Policy Strangles Research and Do-Gooder Intentions Ablaze - Shauna M. Haley (The Scientific World Journal)
Nature starts the news week by chronicling epidemiological researchers’ wrath over how Britain’s General Medical Council (GMC) has implemented the nation’s 1998 Data Protection Act. Science fires up its news with coverage of the torching of two plant labs in the northwestern U.S. by ecoterrorists.